COMPARATIVE ANALYSIS OF COSTS AND PROFITABILITY OF CATFISH FARMING IN NIGER AND LAGOS STATES, NIGERIA - Gomna, Ahmed (Nigerian Journal of Fisheries, 2025)
ABSTRACT The study compared the costs and profitability of catfish farming in Niger and Lagos states, Nigeria. Semi–structured questionnaires were used in collecting data from 100 catfish farmers randomly selected from Niger and Lagos States. The data were analysed using descriptive statistics. Independent samples t-test was used to compare the means of independent samples for test of significance. Costs and profitability of catfish farming in the two states were determined by using a budgetary technique. Average total costs of fish farming in Niger and Lagos States were N 1,069,466and N 1,339,454, respectively. Total variable cost in Niger state was N 1,049,166, compared to N 1,313,354 in Lagos state, accounting for 98 % of the total cost in both states. Feed accounted for 73 % of the total cost of production in Niger and Lagos States. Fixed cost was the lowest cost (2 %) of production in both states. Net return was N 1,870,534 in Niger State and N 2,455,546 in Lagos State. The rate of farm income in Niger State and Lagos State was 64 % and 65 %, respectively. Benefit-cost ratio was 2.7 in Niger State and 2.8 in Lagos State. The Profitability indices showed that catfish farming is profitable in both States.